Cortical Arousal Strategies in Left-Handers during the Aural Perception and Manual Playback of Mono- and Polyphonic Rhythmical Patterns - Pavlovych, Olha S.; Morenko, Alevtyna H.; Kotyk, Olena A.; Vlasiuk, Svitlana S.; Павлович, Ольга Сергіївна; Моренко, Алевтина Григорівна; Котик, Олена Адамівна; Власюк, Світлана Cергіївна (David Publishing Company, 2012)
The actual purpose of this study is to establish the cortical arousal strategies (according to the power of the EEG (electroencephalogram) α-oscillations) during the aural perception as well as manual playback of mono- and polyphonic rhythmical patterns in men with left profile. The study involved 35 men from 19 to 21 years old with the left profile of the manual and aural asymmetries. EEG was recorded in the functional status of rest: during the aural perception and playback of mono- and polyphonic rhythmical patterns with the left and right hand fingers. The monophony in the rhythmical pattern sounding relative to monophonic patterns is followed by more expressed and widespread cortical processes of the EEG α-oscillation depression. Given patterns indicate a greater intensity of ascending nonspecific arousal strategies of data processing by men on conditions of the sound and harmonious complications of the pattern structure. The aural perception and playback of rhythmical patterns with both hands were accompanied by the increased significance of arousal processes in the right hemisphere. This may be due to the dominant role of the hemisphere during the formation of the innervation impacts on the left-hander’s neuro-motor apparatus. More differentiated changes in the cerebral cortex were installed during the left hand activation.
Keywords: Left-handers; mono- and polyphonic sounding; alpha rhythm; rhythmic sense; Лівша; моно - і поліфонічні звуки; альфа ритм; ритмічне відчуття